The object of a criminal offense under Art. 132 of the Criminal Code of Ukraine, through the prism of determining the object of criminal offenses against life and health of a person (Law and Safety, 2021)
Various approaches to defining the object of disclosure of information about the medical examination to detect infection with human immunodeficiency virus or other incurable infectious disease, i.e a criminal offense under Art. 132 of the Criminal Code of Ukraine, are analyzed through the prism of criminal offenses against life and health of a person. The problematic issues of the chosen subject concerning the inconsistency of the object of the criminal offense provided by Art. 132 of the Criminal code of Ukraine, with other criminal offenses against life and health of the person are highlighted. To achieve the goals and objectives of the study, a number of modern general scientific and special methods of scientific cognition were used, such as dialectical, comparative law, system structural, dogmatic, legal (dogmatic) and generalization method. These methods were used together, which contributed to the achievement of the goal and defined tasks. In addition, the study is based on the analysis of domestic regulations governing criminal relations in the field of protection of life and health and confidentiality of information, such as the Constitution of Ukraine, the Criminal Code of Ukraine and other laws of Ukraine. According to the results of the study, for the first time it was proposed to define the object of disclosure of information about a medical examination for human immunodeficiency virus or other incurable infectious disease as a public relationship to protect confidential information about the person, which is confirmed by the study. The thesis on the need to exclude Article 132 from the Criminal Code of Ukraine and expand the content of the disposition of Art. 182 of the Criminal code of Ukraine with such criminally illegal act, as disclosure of information about a medical examination to detect infection with human immunodeficiency virus or other incurable infectious disease is investigated. These results of the study are confirmed by scientific arguments based on a comparative legal study of scientific approaches to defining the object of the outlined criminal offense and analysis of the legal norms of current domestic law.
Keywords: Criminal offense; object of criminal offense; disclosure of information; personal health; honor; dignity.